Nutraceuticals for Functional Feeding and for Drug Discovery in Ruminant Production: A Commentary Paper - Flores, D. A. (Discoveries in Agriculture and Food Sciences, 2025)
The paper lists nutraceuticals from the literature and the world-wide web according to their definition and benefits to nutrition and health. The following nutraceuticals are both novel or have received attention in the literature. They are anti-oxidants, water-soluble carbohydrates (WSC), soluble dietary fibre (SDF), biogenic peptides, functional amino acids (FAA), probiotics, vitamins as pharma, minerals, phytochemicals, “greens” such as herbs, weeds and green forages, omega-3 fatty acids, dietary “bulk” fibre, phytonutraceuticals and adaptogens or anti-stress compounds. The paper then discusses selected topics encountered in the literature or that is still being proposed for the lab bench. They are the: sugars of WSC and SDF, peptides from feed proteins as prebiotics for the rumen stomach and hindgut, prebiotic “bulk” fibre, VitD2,3 analogues as agonists and milk food proteins (MFP). Drug development is suggested of the type by mining the transcriptome and its transcription factors (TF) and the use of peptide nucleic acid (PNA) - based fine-biochemical agents that can be directly applied for therapeutic purposes versus another approach using the low molecular weight (LMW) – proteome in plasma, tissues and secretalogues to find biopharma. An actual e. g. described here not necessarily derived from nutraceuticals but illustrating the use for PNA-carriered TF is to enhance vaccines against Streptococcus pneumoniae, that is, using MR1 protein molecules that activate mucosa-associated invariant T (MAIT) cells in a humeral response against the bacteria that causes pneumonia to be direct applied (DA) by nasal spray applicator. With new perspectives from nutraceuticals, it should be possible to derive new pharma through research drug pipelines to cure, manage incidence or prevent diseases.